Renal Heme Oxygenase-1 Induction with Hemin Augments Renal Hemodynamics, Renal Autoregulation, and Excretory Function - Fady T. Botros; Leszek Dobrowolski; L. Gabriel Navar (International Journal of Hypertension)
Heme oxygenases (HO-1; HO-2) catalyze conversion of heme to free iron, carbon monoxide, and biliverdin/bilirubin. To determine the effects of renal HO-1 induction on blood pressure and renal function, normal control rats (n=7) and hemin-treated rats (n=6) were studied. Renal clearance studies were performed on anesthetized rats to assess renal function; renal blood flow (RBF) was measured using a transonic flow probe placed around the left renal artery. Hemin treatment significantly induced renal HO-1. Mean arterial pressure and heart rate were not different (115±5 mmHg versus 112±4 mmHg and 331±16 versus 346±10 bpm). However, RBF was significantly higher (9.1±0.8 versus 7.0±0.5 mL/min/g, P<0.05), and renal vascular resistance was significantly lower (13.0±0.9 versus 16.6±1.4 [mmHg/(mL/min/g)], P<0.05). Likewise, glomerular filtration rate was significantly elevated (1.4±0.2 versus 1.0±0.1 mL/min/g, P<0.05), and urine flow and sodium excretion were also higher (18.9±3.9 versus 8.2±1.0 μL/min/g, P<0.05 and 1.9±0.6 versus 0.2±0.1 μmol/min/g, P<0.05, resp.). The plateau of the autoregulation relationship was elevated, and renal vascular responses to acute angiotensin II infusion were attenuated in hemin-treated rats reflecting the vasodilatory effect of HO-1 induction. We conclude that renal HO-1 induction augments renal function which may contribute to the antihypertensive effects of HO-1 induction observed in hypertension models.